2004
DOI: 10.1021/ja0491432
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Bimetallic Reactivity:  Hydrogen Activation in Two-Electron Mixed-Valence Compounds

Abstract: Reversible dihydrogen uptake by a two-electron mixed-valence di-iridium complex is examined with nonlocal density-functional calculations. Optimized metrics compare favorably with crystal structures of isolated species, and the calculated activation enthalpy of acetonitrile exchange is accurate within experimental error. Dihydrogen attacks the Ir(2) core at Ir(II); the Ir(0) center is electronically saturated and of incorrect orbital parity to interact with H(2). Isomeric eta(2)-H(2) complexes have been locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 71 publications
8
66
0
Order By: Relevance
“…Phosphazane-bridged binuclear complexes have been proposed to facilitate ligand rearrangements to ligand-bridged intermediates owing to the ligand’s ability to accommodate two-electron changes at the metal core with minimal reorganization energy. 85 The photocrystallography experiments described here support this contention by showing the prevalence of halide-bridged intermediates that preceded M–X bond activation. Although the solid state imposes constraints on the requisite ligand-bridged intermediates, we have leveraged the volatility of carbonyl ligands to allow for the isolation of halide-bridged structures during an interrupted binuclear elimination.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Phosphazane-bridged binuclear complexes have been proposed to facilitate ligand rearrangements to ligand-bridged intermediates owing to the ligand’s ability to accommodate two-electron changes at the metal core with minimal reorganization energy. 85 The photocrystallography experiments described here support this contention by showing the prevalence of halide-bridged intermediates that preceded M–X bond activation. Although the solid state imposes constraints on the requisite ligand-bridged intermediates, we have leveraged the volatility of carbonyl ligands to allow for the isolation of halide-bridged structures during an interrupted binuclear elimination.…”
Section: Discussionsupporting
confidence: 62%
“…21,7784 We have previously proposed a binuclear reductive elimination mechanism for the H 2 evolution step of HX-splitting catalysis with phosphazane-bridged Ir 2 complexes. 85 On the basis of the results shown in Figures 2, 3, and 5, we now observe that a similar mechanism may be operative for halogen photoelimination.…”
Section: Discussionsupporting
confidence: 51%
“…Subsequent DFT calculations support this mechanism and show that addition of H 2 occurs at one metal centre (to give a dihydrogen complex) and passes through a transition structure with a terminal and bridging hydride, finally to rest at a terminal hydride on each Ir centre. [46] [47] Although 20 is a 34-electron cluster, and thus would not be expected to add further H 2 without rupturing the Ir-Ir bond, the bridging iodine moves to a terminal position in the product 21 (3 e -to 1 e -), allowing for overall H 2 addition. Duckett and co-workers have studied a related compound, Ir 2 (dppm) 2 (CO) 2 (µ-S) 2 (24), by using parahydrogen-induced polarisation NMR spectroscopy, and they also showed that the product of addition of H 2 , Ir 2 (dppm) 2 (CO) 2 (H) 2 (µ-S) 2 (25), also loses H 2 upon being purged with N 2 .…”
Section: Equilibrium Reversible (H 2 Is Lost Upon Removal Of the H 2 mentioning
confidence: 99%
“…For other titanocene complexes with four-membered metallacycles [TiPNP], see: Haehnel et al (2012). For selected examples of four-membered metallacycles with a chelating tfepma ligand, see: M = Rh, Esswein et al (2005Esswein et al ( , 2007; M = Ir, Heyduk & Nocera (1999, 2000; Gray et al (2004); Veige et al (2005); Esswein et al (2008). The starting alkyne complex Cp 2 Ti( 2 -Me 3 SiC 2 SiMe 3 ) is described by Burlakov et al (1988).…”
Section: Related Literaturementioning
confidence: 99%